INTENSE TECHNOLOGIES: ILLEGAL TRANSACTIONS ON THE DARK WEB (Journal of Contemporary Issues in Accounting, 2026)
The Dark Web is a concealed segment of the internet that operates beyond the visibility of conventional search engines and can only be accessed through anonymizing technologies such as The Onion Router (Tor). It was originally designed to support privacy, anonymity, and freedom of expression, particularly for journalists, whistleblowers, activists, and individuals living under oppressive or highly monitored environments. However, alongside these legitimate uses, the Dark Web has increasingly become associated with a wide range of criminal and unethical activities. These include drug trafficking, identity theft, illegal arms trade, financial fraud, cyberterrorism, and the exchange of stolen digital assets. This dual nature of the Dark Web as both a protective communication channel and a hub for illicit operations has attracted significant attention from researchers, policymakers, cybersecurity experts, and law enforcement agencies across the globe. Understanding how the Dark Web functions is therefore essential to addressing the risks it poses while preserving its legitimate applications. This paper examines the underlying structure, architecture, and operational mechanisms of the Dark Web, with emphasis on how anonymity networks and hidden services enable both lawful and unlawful interactions. It further explores the broader social, economic, political, and organizational implications of Dark Web activities. Particular focus is placed on the growing threats faced by businesses and institutions, which are increasingly targeted through ransomware attacks, data breaches, intellectual property theft, and reputational damage originating from Dark Web marketplaces and forums. By highlighting these challenges, the paper underscores the urgent need for enhanced monitoring frameworks, advanced analytical techniques, and coordinated response strategies to mitigate the evolving risks associated with the Dark Web ecosystem.
Keywords: Dark Web; Illegal Transactions; Tor Network; Blockchain Forensics